Key Factors of Competitiveness and Sustainability in Livestock Systems of The Andean-Amazonian Piedmont - Pardo Rozo, Yelly Yamparli; Hernández Castorena, Octavio; Andrade Adaime , Milton Cesar (Mercados y Negocios, 2022)
The objective was to identify factors of competitiveness and sustainability in livestock systems of The Andean-Amazonian Piedmont. In a sample of 60 farms in the area, a survey aimed at producers was implemented to identify internal and external factors for competitiveness and sustainability. Data envelopment analysis was used to measure technical efficiency and an econometric model to identify the determinants of competitiveness and sustainability. The key factors towards competitiveness were the profitability of the cattle and the forest extension within the farms. The key factors towards sustainability were the reduction of environmental impacts of deforestation to increase carbon storage and the enhancement of ecosystem services. The increase in profitability and the establishment of sustainable systems of livestock production are the rallying points to improve competitiveness and sustainability in livestock of the Amazonian foothills.